Cycloserine Induced Suicidal Tendencies and Kanamycin Induced Ototoxicity in Indian MDR-TB Patient: A Case Report - Jangra, Manjeet S.; Chhabra, Manik (Current Drug Safety, 2018)
Introduction: Cycloserine and Kanamycin are approved for treatment of multidrug-resistant tuberculosis with good tolerability in Tuberculosis patients and have various labeled adverse reactions but the neuropsychiatric adverse drug reactions with cycloserine are rarely explained. Case Report: We present a case report on Cycloserine induced Suicidal tendencies and Kanamycin induced decrease in hearing sensation in Indian MDR-TB patient. A 55-year-old male patient who was diagnosed with MDR-TB was prescribed with category IV anti-tubercular therapy. Within one month of initiation of therapy, he developed repeated suicidal thoughts, joint pain, restlessness, depression, constipation, insomnia, tinnitus and a decrease in hearing sensation. Results and Discussion: Cycloserine and kanamycin were closely associated with suicidal tendency and tinnitus followed by a decrease in hearing sensations respectively. On causality assessment using WHO-UMC Causality assessment scale, Adverse Drug Reaction with Cycloserine was found to be certain and for kanamycin, ADR was found to be possible. Conclusion: Early management of such fatal ADR can improve the compliance, thus preventing the relapse of infection as well as improving therapeutic outcome in Tuberculosis patients.
Keywords: suicidal tendencies